The Impact of Psycho-Social Interventions on the Wellbeing of Individuals With Acquired Brain Injury During the COVID-19 Pandemic - Wilkie, Lowri; Arroyo, Pamela; Conibeer, Harley; Kemp, Andrew Haddon; Fisher, Zoe (Frontiers in Psychology, 2021)
Individuals with Acquired Brain Injury (ABI) suffer chronic impairment across cognitive, physical and psycho-social domains, and the experience of anxiety, isolation and apathy has been amplified by the COVID-19 pandemic. A qualitative evaluation was conducted of 14 individuals with ABI who had participated in series of COVID adapted group-based intervention(s) that had been designed to improve wellbeing. Eight themes were identified: Facilitating Safety, Fostering Positive Emotion, Managing and Accepting Difficult Emotions, Promoting Meaning, Finding Purpose and Accomplishment, Facilitating Social Ties, (Re)Connecting to Nature, and Barriers to Efficacy. Findings are discussed with respects to recent theoretical developments in positive psychology and wellbeing science and support the use of online and outdoor interventions to enhance wellbeing in individuals living with ABI during the COVID-19 pandemic. This paper makes a unique contribution to second wave positive psychology (PP2.0) through the application of recent advances in wellbeing science to an ABI population during the COVID-19 pandemic. In doing so, this paper lays the foundation for new interventions that not only reduce impairment and distress, but also create opportunities for meaning and enhanced wellbeing in people living with chronic conditions and those individuals living with ABI in particular.